2018
DOI: 10.4314/ahs.v18i4.19
|View full text |Cite
|
Sign up to set email alerts
|

The predictive role of haematological parameters in the diagnosis of osteoarticular brucellosis

Abstract: BackgroundBrucellosis is a zoonosis that affects several systems, especially with the osteoarticular involvement.ObjectivesThis study aims to compare the neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), monocyte/lymphocyte ratio (MLR), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), mean platelet volume (MPV) and red blood cell distribution (RDW) in patients with the osteoarticular involvement and those with non-localised brucellosis and evaluate their predictive value for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…21 A study in Turkey reported that the level of CRP was higher in osteoarticular brucellosis patients than in non-osteoarticular brucellosis patients. 22 Another study reported that patients with the acute brucellosis exhibited higher CRP levels than the control group. 6,13,23 Some other studies have suggested that elevated CRP level may also be associated with disease severity and mortality in hospitalized patients with community-acquired pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…21 A study in Turkey reported that the level of CRP was higher in osteoarticular brucellosis patients than in non-osteoarticular brucellosis patients. 22 Another study reported that patients with the acute brucellosis exhibited higher CRP levels than the control group. 6,13,23 Some other studies have suggested that elevated CRP level may also be associated with disease severity and mortality in hospitalized patients with community-acquired pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the NLR and a decrease in the LMR are considered indicators of systemic inflammation. Several studies have indicated that NLR, PLR, and LMR may predict systemic inflammation, and these markers may be useful in many diseases [13][14][15] . Horne et al 16 reported that NLR is more effective than leukocyte levels in predicting inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the role of peripheral blood leukocyte rates in predicting complications and prognosis in various diseases reported that PLR and NLR rates can be used as prognostic markers with diagnoses. For example, two different studies revealed higher NLR rates in patients requiring amputation in diabetic foot infections and in those with osteoarticular involvement in brucella infection 14,18 . Yapici et al 19 showed in their study that the NLR values of patients who had diabetic foot infection with concurrent osteomyelitis were significantly higher than those without osteomyelitis (p = 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that brucellosis affects the vital organs of the body, including the liver, spleen, joints, etc., their function is impaired and increases or decreases various enzymes and proteins in the body [16]. In some studies, using electrophoresis of proteins in the serum, serum levels of proteins change during infectious diseases that are associated with long-term in ammation.…”
Section: Serum Level Of Vitamin D Crp and Biochemical Parameter In Amentioning
confidence: 99%